Global church planting : biblical principles and best practices for multiplication - Ott, Craig, 1952-; Wilson, Gene, 1953- (Grand Rapids, Mich. : Baker Academic, 2011)
Combining substantive biblical principles and missiological understanding with practical insights, this book walks readers through the various models and development phases of church planting. It emphasizes the role of the missionary church planter, advocating methods that lead to church multiplication.--From publisher description.
The task of church planting -- The reasons for church planting -- New Testament beginnings -- Church multiplication and indigenous church-planting movements -- Apostolic church planters -- The shape of the church -- Pioneer, reproduction, and regional approaches to church planting -- The developmental phases of a church plant : an overview --
Includes bibliographical references (p. 419-441) and index.
Keywords: Church development, New